Digital visual media forensics - Chun-hui FENG; Zheng-quan XU; Xing-hui ZHENG; Li JIANG (Tongxin xuebao)
The origin and concept of digital visual media forensics is introduced, representative double compression de-tection and forgery detection algorithms are introduced in detail afterwards. On this basis, the relationships between dif-ferent forensic algorithms and existing problems of visual media forensic techniques are discussed. Perspectives of the development of digital visual media forensics are put forward in the end.